Can topical epinephrine application to the papilla prevent pancreatitis after endoscopic retrograde cholangiopancreatography? Results from a double blind, multicentre, placebo controlled, randomised clinical trial - Adriana Fabiola Romano-Munive; Miguel Ángel Ramírez-Luna; Luis Uscanga; Felix Tellez-Avila; J Jesus García-Correa; Luis F García-Contreras; José Ramírez-García; Varenka J Barbero-Becerra; Carlos Moctezuma-Velázquez; Jorge A Ochoa-Rubí; Julio Toledo-Cuque; Gerardo Vázquez-Anaya; et al. (BMJ Open Gastroenterology)
Background and study aims Post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) is a complication associated with important morbidity, occasional mortality and high costs. Preventive strategies are suboptimal as PEP continues to affect 4% to 9% of patients. Spraying epinephrine on the papilla may decrease oedema and prevent PEP. This study aimed to compare rectal indomethacin plus epinephrine (EI) versus rectal indomethacin plus sterile water (WI) for the prevention of PEP.Patients and methods This multicentre randomised controlled trial included patients aged >18 years with an indication for ERCP and naive major papilla. All patients received 100 mg of rectal indomethacin and 10 mL of sterile water or a 1:10 000 epinephrine dilution. Patients were asked about PEP symptoms via telephone 24 hours and 7 days after the procedure. The trial was stopped half way through after a new publication reported an increased incidence of PEP among patients receiving epinephrine.Results Of the 3602 patients deemed eligible, 3054 were excluded after screening. The remaining 548 patients were randomised to EI group (n=275) or WI group (n=273). The EI and WI groups had similar baseline characteristics. Patients in the EI group had a similar incidence of PEP to those in the WI group (3.6% (10/275) vs 5.12% (14/273), p=0.41). Pancreatic duct guidewire insertion was identified as a risk factor for PEP (OR 4.38, 95% CI (1.44 to 13.29), p=0.009).Conclusion Spraying epinephrine on the papilla was no more effective than rectal indomethacin alone for the prevention of PEP.Trial registration number This study was registered with ClinicalTrials.gov (NCT02959112).